2004
DOI: 10.1007/s00122-004-1734-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic characterization of an Aegilops tauschii ortholog of the wheat leaf rust disease resistance gene Lr1

Abstract: Aegilops tauschii (goat grass) is the progenitor of the D genome in hexaploid bread wheat. We have screened more than 200 Ae. tauschii accessions for resistance against leaf rust (Puccinia triticina) isolates,which are avirulent on the leaf rust resistance gene Lrl. Approximately 3.5% of the Ae. tauschii accessions displayed the same low infection type as the tester line Thatcher Lrl. The accession Tr.t. 213, which showed resistance after artificial infection with Lrl isolates both in Mexico and in Switzerland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
0
17
2
Order By: Relevance
“…Lr1 is located on chromosome 5D of wheat and Ling et al . () screened > 200 accessions of Ae. tauschii to search for an Lr1 ‐type of gene in the D‐genome donor of bread wheat.…”
Section: Nlr Evolution In Triticeaementioning
confidence: 99%
“…Lr1 is located on chromosome 5D of wheat and Ling et al . () screened > 200 accessions of Ae. tauschii to search for an Lr1 ‐type of gene in the D‐genome donor of bread wheat.…”
Section: Nlr Evolution In Triticeaementioning
confidence: 99%
“…Xpsr567 is an RFLP marker previously mapped to the long arm of chromosome 5D (Xie et al 1993) and shown to be closely linked to Lr1 Gallego et al 1998;Ling et al 2003Ling et al , 2004. Partial resistance gene analog (RGA) sequences 567A (AY123939), 567B (AY123940), and 567C (AY123941) were obtained by sequencing of Aegilops tauschii BAC clones identified with a psr567 probe (Ling et al 2003).…”
Section: Plant Populations and Phenotypic Assessmentmentioning
confidence: 99%
“…A high-resolution map was later published by Ling et al (2003) locating the gene within a 0.16 cM region. This gene is putatively orthologous to a gene in A. tauschii which confers the same resistance phenotype to a number of rust races (Ling et al 2004). A high-density genetic map of the Lr1 locus was constructed and aligned with a physical map obtained by screening the Glenlea BAC library.…”
Section: Introductionmentioning
confidence: 99%
“…However, wild species are most commonly used as donors of disease resistance genes (Jan et al 2002, 2004a, b; Kuhl et al 2001; Ling et al 2004). The dominant monogenic locus Pl ARG originated from the wild species H. argophyllus and is an outstanding source of resistance, because of broad-spectrum resistance against all known races of P. halstedii .…”
Section: Discussionmentioning
confidence: 99%